Concentration levels of radon in mines, industries and dwellings in selected areas of Tororo and Busia districts, Eastern Uganda - Biira, Saphina; Kisolo, Akisophel W.; Mutonyi D’ujanga, Florence (Advances in Applied Science Research, 2014)
Concentration levels and effective exposure dose of radon were determined in mines, industries and dwellings in the Districts of Tororo and Busia, Eastern Uganda in 60 indoor structures between November 2010 and April 2011, using activated charcoal canisters and sodium iodide detector. This study was undertaken to assess the radiological risk of radon exposure in selected areas in Eastern Uganda. The radon concentration levels were found to vary from 28±1 to 97±5 Bqm-3 and the effective dose varied from 0.71±0.03 to 2.44±0.13 mSvy-1, respectively. Over all the mean radon concentration values reported were all below the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) and International Commission on Radiological Protection (ICRP) recommended radon action level of 200 Bqm-3. Some average radon concentration values were close 100 Bqm-3 an action level recommended by World Health Organization (WHO). This means radon levels are still within limits, however necessary mitigation measures need to be taken so that radon levels are not elevated beyond the mean values reported in this work.
Keywords: Radon concentration; Effective dose; Equilibrium equivalent concentration; Activated charcoal canisters; Sodium iodide detector